Synergy between Biodiversity Conservation and Community Empowerment in Mendolo Village - Sari, Nur Nilam; Riyadi, Agus; Kasmuri, Kasmuri; Lijea, Isma. Ae. (Universitas Islam Negeri Walisongo Semarang, Indonesia, 2025)
Mendolo Village is an area of high biodiversity, including five species of Javanese primates and a variety of unique flora and fauna. Biodiversity conservation in high biodiversity areas often faces complex challenges, especially in accommodating the ecological and economic interests of local communities. This research aims to find out the process, program implementation, and impact of synergy of biodiversity conservation and local community empowerment. This research used a qualitative method with a case study approach involving informants through in-depth interviews and participant observation. Data were analyzed using the Miles and Huberman model with triangulation of sources, methods, and time. The results showed that the synergy process starts from (1) identification of village potential, (2) application of participatory approaches, and (3) revitalization of local wisdom. Implementation includes four main programs with significant impacts: economic improvement, social transformation, and ecological restoration.